Encapsulation of Single Plasmonic Nanoparticles within ZIF‐8 and SERS Analysis of the MOF Flexibility. Issue 29 (6th June 2016) - Zheng, Guangchao; de Marchi, Sarah; López‐Puente, Vanesa; Sentosun, Kadir; Polavarapu, Lakshminarayana; Pérez‐Juste, Ignacio; Hill, Eric H.; Bals, Sara; Liz‐Marzán, Luis M.; Pastoriza‐Santos, Isabel; Pérez‐Juste, Jorge
Abstract : Hybrid nanostructures composed of metal nanoparticles and metal‐organic frameworks (MOFs) have recently received increasing attention toward various applications due to the combination of optical and catalytic properties of nanometals with the large internal surface area, tunable crystal porosity and unique chemical properties of MOFs. Encapsulation of metal nanoparticles of well‐defined shapes into porous MOFs in a core–shell type configuration can thus lead to enhanced stability and selectivity in applications such as sensing or catalysis. In this study, the encapsulation of single noble metal nanoparticles with arbitrary shapes within zeolitic imidazolate‐based metal organic frameworks (ZIF‐8) is demonstrated. The synthetic strategy is based on the enhanced interaction between ZIF‐8 nanocrystals and metal nanoparticle surfaces covered by quaternary ammonium surfactants. High resolution electron microscopy and tomography confirm a complete core–shell morphology. Such a well‐defined morphology allowed us to study the transport of guest molecules through the ZIF‐8 porous shell by means of surface‐enhanced Raman scattering by the metal cores. The results demonstrate that even molecules larger than the ZIF‐8 aperture and pore size may be able to diffuse through the framework and reach the metal core. Abstract : A general strategy for the encapsulation of individual metal nanoparticles with the zeolitic imidazolate frameworks ZIF‐8 is described. The presence of plasmonic nanoparticles as cores allows to study the transport of different guest molecules inside the ZIF‐8 shell by means of SERS. The results demonstrate the ability of ZIF‐8 to incorporate molecules larger than the nominal aperture and pore size.